1981
DOI: 10.1126/science.7292016
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Identification of Sites of Antigonadal Action in Mouse Brain

Abstract: Long-term implants releasing a small quantity of melatonin (45 nanograms per day) were used to determine the brain sites of the hormone's antigonadal action in a photoperiodic species, the white-footed mouse (Peromyscus leucopus). Implants in the medial preoptic and supra- and retrochiasmatic areas elicited completed gonadal regression after 7 weeks. Implants in other brain regions had little effect on the animals' reproductive state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
2

Year Published

1985
1985
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(43 citation statements)
references
References 33 publications
3
38
2
Order By: Relevance
“…Studies using intracerebral melatonin implants have however indicated that the photoperiodic effects of melatonin are mediated via a site in or near the hypothalamus (10)(11)(12). The results of the present study show discretely localized high-affinity melatonin receptors restricted to the hypothalamus and epithalamus of the brain and the purs tuberalis of the pituitary.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Studies using intracerebral melatonin implants have however indicated that the photoperiodic effects of melatonin are mediated via a site in or near the hypothalamus (10)(11)(12). The results of the present study show discretely localized high-affinity melatonin receptors restricted to the hypothalamus and epithalamus of the brain and the purs tuberalis of the pituitary.…”
Section: Discussionsupporting
confidence: 55%
“…The localization of these low-affinity receptors within the brain, pituitary and other tissues is remarkably ubiquitous and, as yet, their physiological significance is unknown (4)(5)(6)(7)(8)(9). The widespread distribution found for the low-affinity melatonin receptor contrasts with reports that the photoperiodic effects of melatonin can only be induced by very localized intracerebral administration of the compound (10)(11)(12).…”
contrasting
confidence: 39%
“…Simple SD exposure (Pyter et al 2005a) or administration of melatonin in LD via timed injections (Hall et al 1985) or subcutaneous (Johnston et al 1980a) or central (i.e., anterior hypothalamus) implants (Glass et al 1987) induce gonad regression in white-footed mice (Johnston et al 1980a;Johnston et al 1980b). As with other seasonal breeders, melatonin-induced gonad regression occurs when GnRH release from the hypothalamus is down-regulated (Glass et al 1981;Glass et al 1987), eliminating tonic LH stimulation of the gonads (Glass et al 1988) and ultimately apoptosis of the testes (Young et al 2000). It is surprising that others species do not respond to 6-MBOA as white-footed mice given the similarity in chemical structure between 6-MBOA and melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…Glass and Lynch (14) and Glass and Knotts (13) demonstrated that melatonin-containing pellets implanted in the medial preoptic area, AH, and supra-and retrochiasmatic areas elicit gonadal regression during LD to the same extent as SD exposure. Because melatonin from the pellets was found to diffuse to a distance of only 0.2 mm, and similar doses of melatonin delivered subcutaneously could not trigger testicular regression, it is likely that these neural sites mediate the antigonadal action of melatonin (13,14).…”
Section: Discussionmentioning
confidence: 99%